Liposomes containing NY-ESO-1/tetanus toxoid and adjuvant peptides targeted to human dendritic cells via the Fc receptor for cancer vaccines. (March 2014) - Cruz, Luis J; Rueda, Felix; Simón, Lorena; Cordobilla, Begoña; Albericio, Fernando; Domingo, Joan C
Aim: To improve the immunological response against tumors, a vaccine based on nanoliposomes targeted to the Fcγ-receptor was developed to enhance the immunogenicity of tumor-associated antigens (TAAs).Materials & methods: Using human dendritic cells in vitro, a fragment of the TAA NY-ESO-1 combined with a T-helper peptide from the tetanus toxoid encapsulated in nanoliposomes was evaluated. In addition, peptides Palm-IL-1 and MAP-IFN-γwere coadministered as adjuvants to enhance the immunological response.Results: Coadministration of Palm-IL-1 or MAP-IFN-γpeptide adjuvants and the hybrid NY-ESO-1-tetanus toxoid (soluble or encapsulated in nanoliposomes without targeting) increased immunogenicity. However, the most potent immunological response was obtained when the peptide adjuvants were encapsulated in liposomes targeted to human dendritic cells via the Fc receptor.Conclusion: This targeted vaccine strategy is a promising tool to activate and deliver antigens to dendritic cells, thus improving immunotherapeutic response in situations in which the immune system is frequently compromised, as in advanced cancers.